The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.jaad.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte carcinoma data for Hispanic patients undergoing Mohs micrographic surgery in Miami, Florida from 2011 to 2014

Abstract: BCC, Basal cell carcinoma; SCC, squamous cell carcinoma. *Statistical significance established at P \ .05. y Anatomic locations of tumors were significantly different in the study population. z Area H: mask areas of face (central face, eyelids [including inner/outer canthi], eyebrows, nose, lips [cutaneous/mucosal/vermillion], chin, ear and periauricular skin/sulci, temple), genitalia (including perineal and perianal), hands, feet, nail units, ankles, and nipples/areola.x Area M: cheeks, forehead, scalp, neck,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 9 publications
4
24
0
Order By: Relevance
“…Consistent with prior studies, we found a similar mean age at presentation for Hispanic and NHW individuals with BCC 5 . NHW men presented more frequently with BCC compared with women.…”
Section: Hispanic Individuals (N = 244) Non‐hispanic White Individual...supporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with prior studies, we found a similar mean age at presentation for Hispanic and NHW individuals with BCC 5 . NHW men presented more frequently with BCC compared with women.…”
Section: Hispanic Individuals (N = 244) Non‐hispanic White Individual...supporting
confidence: 91%
“…To our knowledge this finding has not been previously reported. The finding in our study and studies by others, showing that Hispanic individuals are more likely to present with BCC in high‐risk locations, may account for the higher incidence of flap closures we observed 5 . Tissue rearrangement is often required in the high‐risk mask areas of the face to preserve functional anatomy.…”
Section: Hispanic Individuals (N = 244) Non‐hispanic White Individual...supporting
confidence: 73%
See 1 more Smart Citation
“…4 Studies outside the Medicare population have often noted a predominance of BCC in younger patients but with widely varying point estimates of the relative burden of BCC to cSCC. [3][4][5] Finally, data on KCs in patients with skin of color in the United States are limited, mostly to regional 6,7 or single-center [8][9][10][11][12][13][14][15] data. Importantly, none of these prior analyses have attempted to simultaneously analyze and adjust their estimates for age, sex, and race; and given that they derive from geographically restricted populations, the geographic variation in the BCC:cSCC ratio is poorly understood.…”
mentioning
confidence: 99%
“…How ever, the estimate is similar to proportions found in Florida, California and national US databases (91.4%-99.6%). [65][66][67][68]…”
Section: Limitationsmentioning
confidence: 99%